Legal Protection of Women Workers in the Tempuran Industrial Area (A Case Study) - Muhammad Bagus Boy Saputra; Amalia Fadhila Rachmawati (Universitas Muhammadiyah Purworejo, 2021)
Tempuran District which is an industrial area with very rapid development. PT. Usmantex, PT Pandatex and PT Djohartex are companies engaged in textiles whose majority of workers are women. All types of work have risks, especially risks for female workers related to work comfort and safety. For this reason, the protection of the rights of women workers is very important. This study aims to analyze the legal protection for women workers at PT. Djohartex based on Law No. 13 of 2003 concerning employment. The type of method used is juridical empirical with a qualitative approach. This study's findings are the legal protection of female workers at companies in the Tempuran industrial area, especially PT. Djohartex, has not been realized properly due to two obstacles, namely internal factors (lack of employees in the Labor Inspection Unit, limited human resources, limited facilities and infrastructure). infrastructure, the difficulty of supervision time), external factors (lack of awareness of the company and lack of cooperation between the parties).